2015
DOI: 10.1227/neu.0000000000000596
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Ruptured Middle Cerebral Artery Aneurysms With Large Intraparenchymal or Sylvian Fissure Hematomas

Abstract: MCA aneurysm rupture with concomitant large intraparenchymal or sylvian fissure hematoma formation carries a grave prognosis. Simultaneous hematoma evacuation and aneurysm clipping with or without craniectomy can be an effective treatment modality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 36 publications
(36 reference statements)
0
14
1
Order By: Relevance
“…A separate and often-cited advantage of microsurgical clipping of ruptured MCA aneurysms is the ability to evacuate an IPH or perform a decompressive hemicraniectomy promptly in the same surgical setting. 18,20,23 In our series, one-half of the 46 patients had IPH associated with aneurysm rupture, and 7 (14%) of them required a decompressive craniotomy. Notably, in the series of endovascularly treated ruptured MCA aneurysms by Mortimer et al, 14 8.2% (20 of 244) of patients underwent surgery for IPH evacuation or decompressive craniotomy after endovascular treatment of the aneurysm.…”
Section: Discussionmentioning
confidence: 64%
“…A separate and often-cited advantage of microsurgical clipping of ruptured MCA aneurysms is the ability to evacuate an IPH or perform a decompressive hemicraniectomy promptly in the same surgical setting. 18,20,23 In our series, one-half of the 46 patients had IPH associated with aneurysm rupture, and 7 (14%) of them required a decompressive craniotomy. Notably, in the series of endovascularly treated ruptured MCA aneurysms by Mortimer et al, 14 8.2% (20 of 244) of patients underwent surgery for IPH evacuation or decompressive craniotomy after endovascular treatment of the aneurysm.…”
Section: Discussionmentioning
confidence: 64%
“… 16 Recent studies have indicated that simultaneous hematoma evacuation and aneurysmal clipping with or without craniectomy can be an effective treatment modality for poor-grade middle cerebral artery aneurysms. 17 Along with the advances in microneurosurgical techniques and development of microneurosurgical instrumentation, “keyhole” (mini bone flap) approach has been applied to aneurysmal clipping, and be equally likely to obtain a good outcome. 18 Furthermore, external ventricular drainage (EVD) could reduce the intracranial pressure and has been proved to be indicative of increased likelihood favorable outcome for poor-grade aneurysms.…”
Section: Introductionmentioning
confidence: 99%
“…Vascular malformations that can lead to SICH include arteriovenous malformations (23), cerebral aneurysms (24), dural arteriovenous fistulas (25), and cavernous malformations (26). Patients who have had ischemic strokes can experience hemorrhagic conversion (27), as can up to 50% of cerebral venous thrombosis patients (28).…”
Section: Sich Etiologymentioning
confidence: 99%